2021
DOI: 10.1177/15330338211037813
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 Polymorphisms Have Significant Associations With Cancer Risk, Especially Feminine Cancer

Abstract: Background: The plasminogen activator inhibitor-1 (PAI-1) was found in many types of tumor cells, which involved in tumorigenesis. Some studies investigated the associations between PAI-1 polymorphisms and various cancers, but the results were inconsistent. So this study did a meta-analysis to assess the strength of relationship between PAI-1 and cancer. Methods: Articles that meet the requirements were searched from PubMed, EMBASE, MEDLINE, Scopus, CNKI, Wanfang and SinoMed electronic databases before June 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…Indeed, uPA and PAI-1 are among the most highly induced proteins in several migratory or invasive tumor cell types. Even though some studies failed to show a correlation between elevated levels of PAI-1 and poor clinical prognosis (13)(14)(15) , PAI-1 has been established as one of the most reliable biomarkers and prognostic markers in many cancer types, including breast (16)(17)(18) , ovarian (19) , bladder (20,21) , colon (22) , renal (23) and non-small cell lung cancers (24) .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, uPA and PAI-1 are among the most highly induced proteins in several migratory or invasive tumor cell types. Even though some studies failed to show a correlation between elevated levels of PAI-1 and poor clinical prognosis (13)(14)(15) , PAI-1 has been established as one of the most reliable biomarkers and prognostic markers in many cancer types, including breast (16)(17)(18) , ovarian (19) , bladder (20,21) , colon (22) , renal (23) and non-small cell lung cancers (24) .…”
Section: Resultsmentioning
confidence: 99%
“…A robust correlation between tumor malignancy and PAI-1 expression has been demonstrated [27][28][29] . To better understand the tumor cells highly expressing PAI-1, we analyzed B16F10, a murine melanoma subline with high lung metastatic ability, and B16F1, a subline with low metastatic ability.…”
Section: Pai-1 Induces Pd-l1 Expression In Various Types Of Tumor Cellsmentioning
confidence: 93%
“…On review of the recent studies, other identified adipocytokines, including plasminogen activator inhibitor-1 (PAI-1) ( Wang et al, 2021 ), and fatty acid-binding protein 4 (FABP4) ( Wu et al, 2021 ), also play important roles in regulating various physiological processes. Of note, these adipocytokines have considerable consequences for promoting the proliferation and migration of endometrial cancer cells and may be possible targets for the therapy.…”
Section: Manuscript Formattingmentioning
confidence: 99%